Políticas públicas na educação: a migração venezuelana no espaço escolar e urbano do Município de Pacaraima - Roraima - Nascimento, Karen Rebecca Camurça do (2020)
This research addresses the theme of public policies on education reflecting on the impacts of Venezuelan migration on the school and urban space of the municipality of Pacaraima - Roraima border (Brazil - Venezuela), with the general objective of analyzing public policies in the area of education on the Brazil-Venezuela border, investigating the effects of the migratory context of this public service on Brazilians and Venezuelans. The research methodology is characterized as descriptive, bibliographic, and qualitative, under a systemic methodological approach, exploratory and participatory. Thus, analyzing the concepts of public policies and their use in society, identifying and verifying in this way, the public policies offered in the area of education, which serve Brazilians and Venezuelans affected by the impacts of migration in the municipality of Pacaraima.